2016
DOI: 10.1093/mnras/stw2870
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy cluster's rotation

Abstract: We study the possible rotation of cluster galaxies, developing, testing and applying a novel algorithm which identifies rotation, if such does exist, as well as its rotational centre, its axis orientation, rotational velocity amplitude and, finally, the clockwise or counterclockwise direction of rotation on the plane of the sky. To validate our algorithms we construct realistic Monte Carlo mock rotating clusters and confirm that our method provides robust indications of rotation. We then apply our methodology … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 58 publications
(68 reference statements)
1
46
0
Order By: Relevance
“…In order to account for the detected temperature anisotropy, however, the M81 halo should be filled by a relatively large amount of gas (likely in the form of cold gas clouds), as in the models proposed, e.g., by Pfenniger et al (1994);De Paolis et al (1995a); Gerhard & Silk (1996). A viable explanation of the detected effect could be, in principle, also the rotational kinematic Sunyaev-Zel'dovich (rkSZ) effect, which is known to be active on galaxy cluster scales (Cooray et al 2002;Chluba et al 2002;Manolopoulou et al 2017). Naturally, to be active, the rkSZ effect does require the presence of a conspicuous population of high energy electrons in the rotating M81 halo.…”
Section: Discussionmentioning
confidence: 80%
“…In order to account for the detected temperature anisotropy, however, the M81 halo should be filled by a relatively large amount of gas (likely in the form of cold gas clouds), as in the models proposed, e.g., by Pfenniger et al (1994);De Paolis et al (1995a); Gerhard & Silk (1996). A viable explanation of the detected effect could be, in principle, also the rotational kinematic Sunyaev-Zel'dovich (rkSZ) effect, which is known to be active on galaxy cluster scales (Cooray et al 2002;Chluba et al 2002;Manolopoulou et al 2017). Naturally, to be active, the rkSZ effect does require the presence of a conspicuous population of high energy electrons in the rotating M81 halo.…”
Section: Discussionmentioning
confidence: 80%
“…First of all, we should keep in mind that the two-body model does not consider the angular moment of the system, which is unlikely to be zero, since we have identified a velocity assymetry around the principal axis of the galaxy projected distribution, suggesting a rotating object. The reason this could be important to any dynamical analysis is that the corrected cluster mass can be reduced by ∼20%-30%, on average, with respect to that uncorrected for rotation, as shown in Manolopoulou & Plionis (2016). An additional weakness of the two-body model is not considering the distribution of matter inside each cluster.…”
Section: Caveats About the Methodsmentioning
confidence: 99%
“…Also note that in some clusters the rotation pattern may be hidden because the system is viewed face on, as suggested in the case of Abell 1835 by McNamara et al (2014). It has also been suggested that a significant fraction (∼ 25%) of clusters may rotate coherently on Mpc scales with typical velocities of a few hundreds of km s −1 (Manolopoulou & Plionis 2017; see also Bianconi et al 2013). Finally, the presence of cool core cold fronts, i.e.…”
Section: Introductionmentioning
confidence: 87%